FROM TRADITIONAL TO DIGITAL: THE READINESS OF SMALL ENTREPRENEURS FOR ONLINE BUSINESS EXPANSION - Azli Umar; Nor Fadzilah Zainal; Nor Hidayah Harun; Siti Nur Fathini Muhsain; Aniza @ Mazita Ishak; Mohd Sukor Md Yusoff; Muhammad Shfri Daie, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
The rapid advancement of the digital era has revolutionized societal lifestyles, streamlining daily activities such as buying and selling. However, many small entrepreneurs remain unaware of the critical role digital transformation plays in expanding their businesses globally. To address this gap, a preliminary survey was conducted to assess the interest and readiness of small entrepreneurs in leveraging digital technology for business growth. This study aims to explore the challenges and needs of small business owners in adopting digital tools for marketing and expansion. A quantitative survey approach was employed, involving 30 small entrepreneurs who participated in the Digital Marketing Workshop at the National Information Dissemination Centre (NADI) Bertam, Penang. Data were collected through structured questionnaires distributed to all participants. The findings highlight significant barriers to digital adoption, with limited computer literacy emerging as the primary challenge. Many entrepreneurs struggle with basic digital tools essential for effective marketing, while restricted internet access further hinders their ability to implement online strategies. Additionally, a lack of knowledge in key digital marketing techniques, such as search engine optimization (SEO), social media marketing, and email marketing, prevents them from maximizing their business potential in the digital landscape. The study provides crucial insights for policymakers and industry stakeholders to design targeted intervention strategies that address these challenges. By equipping small entrepreneurs with essential digital skills and knowledge, they can confidently embrace technological advancements and unlock new opportunities for business expansion. Strengthening digital literacy among small business owners is vital to ensuring their sustainability and competitiveness in the evolving digital economy.